Impolitic pictures: providence, history, and the iconography of Protestant nationhood in early Stuart England - Walsham, Alexandra (Studies in church history, 1997)
This paper explores the religious politics of remembering and visually depicting the recent past in early modern England. In the first quarter of the seventeenth century, the commemoration of a series of critical moments in the reigns of the last Tudor monarch, Elizabeth, and her Stuart successor, King James I, became a powerful bulwark of both Church and State. The story of the nation’s providential rescues from Catholic treachery and oppression, pre-eminently the defeat of the Spanish Armada and the discovery of the Gunpowder Plot, evolved into an enduring myth which fused Protestantism with patriotism - a myth which, moreover, engendered its own highly emotive iconography. By the 1630s, however, the celebration of these same anniversaries grew increasingly contentious: as the theological complexion of the episcopal hierarchy gradually shifted, such events became the victims of a species of ecclesiastical amnesia. Caroline clerics began to take deliberate steps to discourage retrospection, to control the memory of historical milestones which were now regarded as a source of embarrassment. Here I want to suggest tentatively that this trend can be traced into the realm of pictorial representation. In the process, we may learn something more about the relationship between the Calvinist strand of the Reformation and the graphic arts.